Rewriting Reproductive Rights: Applying Feminist Methodology to the European Court of Human Rights' Abortion Jurisprudence - Sauls Avolio, Vanessa (feminists@law, 2017)
This article adopts feminist methodology to demonstrate how women’s rights and reproductive freedom can be enhanced at the judicial level: a process that can lead to legal reform. The practice of feminist judgment-writing is central in achieving this objective. Recently, feminist scholars and practitioners have come together to rewrite landmark judgments concerning women’s rights. Examples of these efforts can be found in the Women’s Court of Canada and the UK Feminist Judgments Project. Drawing from these reformative experiences, the article rewrites two abortion judgments of the European Court of Human Rights: A, B and C v Ireland and P and S v Poland. These revisions emphasise the necessity for alternate accounts of women’s rights in the courtroom.